Pengaruh Komitmen Organisasi Dan Gaya Kepemimpinan Terhadap Hubungan Antara Partisipasi Anggaran Dan Kinerja Manajerial (Studi Empiris Pada Kantor Cabang Perbankan Di Propinsi Lampung) - Evi Yuniarti; Fadila Marga Satya (Jurnal Ilmiah ESAI, 2008)
The effect of participation in the budgeting process to improve managerial performance has been an interesting area of research for many years.  It has been postulated that participative budgeting has a positive effect on managerial performance.  Several prior researchers, held to examine the relationship between participative budgeting and managerial performance, have yielded the inconsistent result.  To overcome this phenomenon, some researchers suggest using contingency approach which looks at the moderating effect of organizational comitment and leadership styles. This research examined the effect of organizational commitment and leadership styles on the effectiveness of participative budgeting to increase managerial performance.  The responses from 25 heads from Lampung banking companies to a questionnaire survey designed to measure the variables, were analyzed using a multiple regression model.  The result indicated that there is no significant effect between participative budgeting and managerial performance. In addition, both organizational commitment and leadership styles don’t moderate the relationship between participative budgeting and managerial performance.   Keywords :  participative budgeting, organizational commitment, leadership styles, and managerial performance.